Novel exciton dissociation behavior in tin-lead organohalide perovskites. (September 2016) - Lin, Guoming; Lin, Yuanwei; Huang, Huan; Cui, Rongli; Guo, Xihong; Liu, Bing; Dong, Jinquan; Guo, Xuefeng; Sun, Baoyun
Abstract: The design of organic-inorganic trihalide perovskite solar cells with higher performance, lower environmental pollution, lower cost and easier of fabrication should be a significant stride towards their practical application. Nevertheless, the contribution of exciton dissociation behavior of the perovskite to this strategy has not been recognized comparing with film morphology, device architecture and fabrication process. Here we demonstrated a series of solution-processed solid-state tin-lead organohalide perovskite photovoltaic solar cells using carefully selected fullerene derivatives as the electron transport layer. The hybrid excitonic feature of CH3 NH3 Sn0.5 Pb0.5 I3 was revealed for the first time by comparing the exciton dissociation behaviors of CH3 NH3 Sn0.5 Pb0.5 I3 with conventional excitonic semiconductor in both planar heterojunction solar cells and lateral architecture photosensors. By optimizing the lowest unoccupied molecular orbital level of electron transport layer materials, high open circuit voltage of 0.69 V, short circuit photocurrent density of 22.8 mA cm −2 and power conversion efficiency of more than 10% were achieved with the incident photon conversion efficiency spectra onset reaching 1050 nm. These devices may work as high performance photodetectors with a broad spectral response expanding from UV–visible to near-infrared. Our results have suggested the exciton dissciation behavior to be an efficient perspective for the improvement of provskite solar cells. Graphical abstract: Highlights: Several novel fullerene derivatives were synthesized as the electron transport layer for tin-lead perovskite solar cells. Power conversion efficiency of 10% were achieved with incident photon conversion efficiency spectra onset reaching 1050 nm. The hybrid excitonic feature of tin-lead perovskite (CH3 NH3 Sn0.5 Pb0.5 I3 ) was reported for the first time.